Achieving over 11% power conversion efficiency in PffBT4T-2OD-based ternary polymer solar cells with enhanced open-circuit-voltage and suppressed charge recombination. (February 2018) - Li, Wei; Cai, Jinlong; Cai, Feilong; Yan, Yu; Yi, Hunan; Gurney, Robert S.; Liu, Dan; Iraqi, Ahmed; Wang, Tao
Abstract: Fabricating ternary solar cells (TSCs) is a promising strategy to improve the power conversion efficiency of organic photovoltaics without introducing sophisticated processing procedures. We report in this work high efficiency TSCs with the maximum PCE over 11% by introducing a medium band gap conjugated polymer PCDTBT8 into the PffBT4T-2OD:PC71 BM binary photovoltaic system. Morphological investigation shows that the third component PCDTBT8 locates at the interface between PffBT4T-2OD and PC71 BM without disrupting the crystallization of PffBT4T-2OD to maintain decent charge mobility, and loosens the fullerene aggregation networks to facilitate exciton dissociation. The efficient Förster energy transfer from PCDTBT8 to PffBT4T-2OD enables the ternary devices to retain a high short-circuit current density despite the slightly decreased light absorption. Device physics studies suggest that the addition of PCDTBT8 can enhance the built-in voltage, prolong the carrier lifetime, reduce the defect density and suppress the trap-assisted charge recombination, leading to an improved FF and VOC to enhance the efficiency of ternary devices. Graphical abstract: High efficiency ternary polymer solar cell with a maximum PCE of 11.2% was achieved by introducing a medium band gap polymer PCDTBT8 into the crystalline PffBT4T-2OD and PC71 BM binary photovoltaic system. Highlights: PCEs over 11% were achieved in PffBT4T-2OD:PCDTBT8:PC71 BM ternary solar cells. Förster energy transfer from PCDTBT8 to PffBT4T-2OD was determined. PCDTBT8 locates at PffBT4T-2OD/PC71 BM interface without disrupting the crystallization. PCDTBT8 enhances built-in voltage, and suppresses trap-assisted charge recombination.